Comparison of Cryptography Algorithms for Mobile Payment Systems - Aydın, Muhammed; Sertbaş, Ahmet; ŞENGEL, ÖZNUR (My University, 2018)
Mobile payment services are the newest and most popular technology that is developing according to our habits and needs. Consumer all over the world are using mobile phone for payment as well as communication. The main purpose of using mobile payment application is doing all transaction easily and quickly. Not only data security in electronic transactions, but also the speed of the system operations is becoming very important. There is a threshold value to finish all transaction in mobile payment systems. If the security algorithm is more complex and exceed threshold, it is not suitable to using in mobile payment systems. In this paper we compare cryptography algorithms and proposed two algorithms on Advanced Encryption Standards. The experiment results show that proposed algorithms is suitable cryptography algorithm for mobile system according to time and storage consumption factors.